2020
DOI: 10.1101/2020.05.28.119206
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cryo-EM Structure of Native Human Uromodulin, a Zona Pellucida Module Polymer

Abstract: SUMMARYAssembly of extracellular filaments and matrices mediating fundamental biological processes such as morphogenesis, hearing, fertilization and antibacterial defense is driven by a ubiquitous polymerization module known as zona pellucida (ZP) “domain”. Despite the conservation of this element from hydra to human, no information is available on the filamentous conformation of any ZP module protein. Here we report the cryo-electron microscopy structure of uromodulin (UMOD)/Tamm-Horsfall protein, the most ab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 97 publications
1
5
0
Order By: Relevance
“…Notably, our data also do not support the UMOD architecture suggested by a recent tomographic analysis, where polymers are made up of ZP modules that simply stack in a zig‐zag manner, without any conformational change of the interdomain linker and associated separation of ZP‐N and ZP‐C (Weiss et al , 2020). On the other hand, our results are in agreement with a study of the UMOD filament core (Stanisich et al , 2020) that appeared while this work was under revision and publicly available as a preprint version (preprint: Stsiapanava et al , 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Notably, our data also do not support the UMOD architecture suggested by a recent tomographic analysis, where polymers are made up of ZP modules that simply stack in a zig‐zag manner, without any conformational change of the interdomain linker and associated separation of ZP‐N and ZP‐C (Weiss et al , 2020). On the other hand, our results are in agreement with a study of the UMOD filament core (Stanisich et al , 2020) that appeared while this work was under revision and publicly available as a preprint version (preprint: Stsiapanava et al , 2020).…”
Section: Discussionsupporting
confidence: 92%
“…This UMOD assembly model is analogous to the recently proposed assembly mechanism of filamentous type V pili, in which assembly is linked with proteolytic release of pilus subunits from the outer bacterial membrane ( Shibata et al, 2020 ). During the preparation of this manuscript, a related preprint article on the cryo-EM structure of the UMOD filament core was published ( Stsiapanava et al, 2020 ). In said study, an alternative model of UMOD assembly was proposed, based on the assumption that assembly starts from membrane-bound pro-UMOD homodimers.…”
mentioning
confidence: 99%
“…In proteins like uromodulin that have polymerizing ZPn domains, ZPc domains are thought to inhibit the ZPn domain [30]. While our study was under review, two groups reported cryo-EM structures for full-length uromodulin that suggest filament assembly involves interactions of both ZPn and ZPc domains with linker regions of other monomers, which would suggest that both domains are functionally important [69,70]. In the TGFβ receptors Betaglycan and Endoglin, ZPc domains dimerize and can bind ligands, but have not been reported to form higher-order structures [28,29,71].…”
Section: Zpc Domains Can Function Independently Of Zpn Domainsmentioning
confidence: 90%